Assessment of spatio-temporal status and trends of electric vehicle adoption in Thailand - Supawadee Srimongkol; Pramanik, Malay Kumar; Tripathi, Nitin Kumar; Tsusaka, Takuji W.; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
While electric vehicle (EV) adoption is accelerating globally, research has disproportionately focused on high-income countries, leaving a critical gap in understanding how adoption unfolds in emerging economies. In Southeast Asia, including Thailand, regional disparities, infrastructure limitations, and behavioral challenges complicate the transition to low-carbon mobility. This study examines the spatio-temporal trends and key factors influencing EV adoption in Thailand between 2019 and 2024. Using a mixed-methods approach, it combines GIS-based spatial analysis, a structured driver survey, and binary logistic regression to analyze regional patterns and determinants of EV ownership. The research also reviews policy documents to contextualize findings within Thailand{u2019}s evolving electric mobility landscape. Results reveal that EV adoption is growing rapidly in urban areas like Bangkok and the Eastern Economic Corridor (EEC), while rural provinces lag due to limited charging infrastructure and lower public awareness. Logistic regression shows that age, occupation, awareness of charging stations, and perceived cost-effectiveness significantly influence adoption. Contrary to earlier assumptions,respondents with firsthand EV experience and awareness of government incentives were more likely to adopt EVs, emphasizing the role of exposure and policy clarity in shaping behavior. Based on these findings, the study prioritizes five interrelated policy actions: (1) expanding visible and accessible charging infrastructure, (2) enhancing public awareness campaigns grounded in real user experience, (3) improving the clarity and delivery of financial incentives, (4) promoting equitable EV access in rural areas, and (5) fostering local public{u2013}private collaboration. Among these, infrastructure visibility and affordability emerged as the most influential factors offering clear direction for targeted interventions.This study advances the literature by integrating spatial, behavioral, and policy dimensions, offering a regionally grounded framework for EV promotion in developing economies.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Development and Sustainability
Thesis (M. Sc.) - Asian Institute of Technology, 2025
Keywords: Electric veshicles -- Thailand; Electric vehicles -- Statistical methods; Spatial analysis (Statistics)